(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problems of aggressive behavior in adolescence. The relevance of her research in the context of global social transformations is noted. Some approaches to the interpretation of a certain concept are considered. An attempt is made to systematize the leading factors of adolescent aggressiveness. The role of the reference environment and family education as possible catalysts of aggressiveness at this age is noted. The specifics of teenage aggression in connection with the age crisis and the processes of intensification of self-awareness are revealed. Typologies and classifications of aggressiveness are presented, some characterological characteristics of the personality of an aggressive teenager are highlighted.